2011
DOI: 10.1002/rra.1505
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Aquatic Weeds Greatly Enhances Fish Community Richness and Diversity: An Example From the Burdekin River Floodplain, Tropical Australia

Abstract: Hydrological changes associated with irrigation, in conjunction with increased nutrient concentrations and aquatic plant densities, have greatly impacted fish habitat values on the Burdekin River floodplain. The two most significant weeds in the Burdekin floodplain are water hyacinth (Eichhornia crassipes) and para grass (Urochloa mutica). Water hyacinth creates a base for the para grass (and then other weeds) to grow out into deeper water, creating weed mats that can then only be removed by mechanical means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 20 publications
0
41
0
1
Order By: Relevance
“…Spencer et al 2006;Arthur et al 2007;Wu and Wu 2007;O'Sullivan et al 2010;Perna et al 2012). In contrast to submerged species, floating leaved species such as Eichhornia crassipes or Trapa natans, but also emergent species such as Ludwigia spp.…”
Section: Integrating Macrophyte Species Characteristicsmentioning
confidence: 99%
“…Spencer et al 2006;Arthur et al 2007;Wu and Wu 2007;O'Sullivan et al 2010;Perna et al 2012). In contrast to submerged species, floating leaved species such as Eichhornia crassipes or Trapa natans, but also emergent species such as Ludwigia spp.…”
Section: Integrating Macrophyte Species Characteristicsmentioning
confidence: 99%
“…Macrophyte invaders cause troubles in ecosystems all over the world (e.g., Pieterse and Murphy, 1990), and they can change the composition and reduce diversity of aquatic assemblages (Douglas and O'Connor, 2003;Perna et al, 2012;Amorim et al 2015). The macrophyte Urochloa arrecta (Hack.…”
Section: (With 2 Figures)mentioning
confidence: 99%
“…Large woody debris and submerged aquatic vegetation add structural complexity that can create habitat conditions conducive to some fish species (Quist et al 2005). In addition, Perna et al (2012) found the removal of floating weed improved the quality of physical habitat and led to the re-establishment of many native fish species. Biotic factors of predation and competition further act to filter fish assemblage structure through the processes of niche segregation and resource partitioning (Jackson et al 2001).…”
Section: Introductionmentioning
confidence: 98%